Rapamycin improves healthspan but not inflammaging in nfκb1−/− mice. Issue 1 (23rd November 2018) - Correia‐Melo, Clara; Birch, Jodie; Fielder, Edward; Rahmatika, Dina; Taylor, Jennifer; Chapman, James; Lagnado, Anthony; Carroll, Bernadette M.; Miwa, Satomi; Richardson, Gavin; Jurk, Diana; Oakley, Fiona; et al.
Abstract: Increased activation of the major pro‐inflammatory NF‐κB pathway leads to numerous age‐related diseases, including chronic liver disease (CLD). Rapamycin, an inhibitor of mTOR, extends lifespan and healthspan, potentially via suppression of inflammaging, a process which is partially dependent on NF‐κB signalling. However, it is unknown if rapamycin has beneficial effects in the context of compromised NF‐κB signalling, such as that which occurs in several age‐related chronic diseases. In this study, we investigated whether rapamycin could ameliorate age‐associated phenotypes in a mouse model of genetically enhanced NF‐κB activity ( nfκb1 −/− ) characterized by low‐grade chronic inflammation, accelerated aging and CLD. We found that, despite showing no beneficial effects in lifespan and inflammaging, rapamycin reduced frailty and improved long‐term memory, neuromuscular coordination and tissue architecture. Importantly, markers of cellular senescence, a known driver of age‐related pathology, were alleviated in rapamycin‐fed animals. Our results indicate that, in conditions of genetically enhanced NF‐κB, rapamycin delays aging phenotypes and improves healthspan uncoupled from its role as a suppressor of inflammation.